"User sensitive inclusive design" - in search of a new paradigm - Newell, Alan F.; Gregor, Peter (Proceedings on the 2000 conference on Universal Usability, 2000)
This paper considers appropriate research methodologies for the development of Universal Usability. It is written from the viewpoint of research which has the long term objective of developing technological systems for everyone, including people with disabilities. It considers whether new research paradigms are appropriate and how they are different from those used within traditional technological research. It suggests the development of a new paradigm of “User Sensitive Inclusive Design” which includes people with disabilities within a User Centred Design methodology, and recommends a collaborative approach to the development of such a methodology.
KerkoCite.ItemAlsoKnownAs: 10.1145/355460.355470 2339240:8MBZDCBK 2405685:LP4C6FMU
Keywords: universal design; usability; user centered design